Effectiveness of personalised risk information and taster sessions to increase the uptake of smoking cessation services (Start2quit): a randomised controlled trial - Gilbert, Hazel (Lancet, 2017)
BACKGROUND: National Health Service Stop Smoking Services (SSSs) offer help to smokers motivated to quit; however, attendance rates are low and recent figures show a downward trend. We aimed to assess the effectiveness of a two-component personalised intervention on attendance at SSSs. METHODS: We did this randomised controlled trial in 18 SSSs in England. Current smokers (aged ≥16 years) were identified from medical records in 99 general practices and invited to participate by their general practitioner. Individuals who gave consent, were motivated to quit, and had not attended the SSS within the past 12 months, were randomly assigned (3:2), via computer-generated randomisation with permuted blocks (block size of five), to receive either an individually tailored risk letter and invitation to attend a no-commitment introductory session run by the local SSS (intervention group) or a standard generic letter advertising the local SSS (control group). Randomisation was stratified by sex. Masking of participants to receipt of a personal letter and invitation to a taster session was not possible. The personal letter was generated by a research assistant, but the remainder of the research team were masked to group allocation. General practitioners, practice staff, and SSS advisers were unaware of their patients' allocation. The primary outcome was attendance at the first session of an SSS course within 6 months from randomisation. We did analysis by intention to treat. This trial is registered with Current Controlled Trials, number ISRCTN 76561916. FINDINGS: Recruitment, collection of baseline data, delivery of the intervention, and follow up of participants took place between Jan 31, 2011, and July 12, 2014. We randomly assigned 4384 smokers to the intervention group (n=2636) or the control group (n=1748); 4383 participants comprised the intention-to-treat population. Attendance at the first session of an SSS course was significantly higher in the intervention group than in the control group (458 [17·4%] vs 158 [9·0%] participants; unadjusted odds ratio 2·12 [95% CI 1·75–2·57]; p<0·0001). INTERPRETATION: Delivery of personalised risk information alongside an invitation to an introductory session more than doubled the odds of attending the SSS compared with a standard generic invitation to contact the service. This result suggests that a more proactive approach, combined with an opportunity to experience local services, can reduce patient barriers to receiving treatment and has high potential to increase uptake. FUNDING: National Institutes of Health Research Health Technology Assessment.